The Effect of Negative Stigma of Covid-19 on Nurse Performance - Raimunda Woga; Irwan Budiana; Marieta KS Bai; Dewi Nur Sukma Purqoti; Agus Supinganto; Mfuh Anita Y. Lukong (Universitas STRADA Indonesia, 2022)
Negative stigmatization of nurses is one of the challenges in preventing and controlling Covid-19 in hospitals. The purpose of this study was to determine the effect of the negative stigma of Covid-19 on the performance of nurses. This research uses a quantitative design method with a correlational analytic approach. Data processing using the data analysis test in this study was carried out using the Spearman Rank correlation test with the help of the SPSS for windows 19.00 program. Based on the results of the Linearity Regression test, the stigmatization variable Covid-19 has no effect on the performance of nurses in East Nusa Tenggara Province and West Nusa Tenggara Province also has an influence on nurse performance. Nurses as part of the disaster management team should not receive negative stigmatization. This of course has an unfavorable impact on the performance of nursing staff.